Carotid Intima-Media thickness progression and risk of vascular events in people with Diabetes: Results from the PROG-IMT collaboration - Lorenz, M.; Price, J.; Robertson, C.; Bots, M.; Polak, J.; Poppert, H.; Kavousi, M.; Dorr, M.; Stensland, E.; Ducimetiere, P.; Ronkainen, K.; Kiechl, S.; et al. (American Diabetes Association, 2015)
© 2015 by the American Diabetes Association. OBJECTIVE Carotid intima-media thickness (CIMT) is a marker of subclinical organ damage and predicts cardiovascular disease (CVD) events in the general population. It has also been associated with vascular risk in people with diabetes. However, the association of CIMT change in repeated examinations with subsequent CVD events is uncertain, and its use as a surrogate end point in clinical trials is controversial. We aimed at determining the relation of CIMT change to CVD events in people with diabetes. RESEARCH DESIGN AND METHODS In a comprehensive meta-analysis of individual participant data, we collated data from 3,902 adults (age 33-92 years) with type 2 diabetes from 21 populationbased cohorts. We calculated the hazard ratio (HR) per standard deviation (SD) difference inmean common carotid artery intima-media thickness (CCA-IMT) or in CCA-IMT progression, both calculated from two examinations on average 3.6 years apart, for each cohort, and combined the estimates with random-effects meta-analysis. RESULTS Average mean CCA-IMT ranged from 0.72 to 0.97mmacross cohorts in peoplewith diabetes. The HR of CVD events was 1.22 (95% CI 1.12-1.33) per SD difference in mean CCA-IMT, after adjustment for age, sex, and cardiometabolic risk factors. Average mean CCA-IMT progression in people with diabetes ranged between 20.09 and 0.04 mm/year. The HR per SD difference in mean CCA-IMT progression was 0.99 (0.91-1.08). CONCLUSIONS Despite reproducing the association between CIMT level and vascular risk in subjects with diabetes, we did not find an association between CIMT change and vascular risk. These results do not support the use of CIMT progression as a surrogate end point in clinical trials in people with diabetes.